Karakteristik dan Faktor Penyebab Permukiman Kumuh di Kelurahan Tanjung Mas Kota Semarang - Salma, Muvidayanti; Sriyono, Sriyono (Geo-Image, 2019)
Tanjung Mas is one of the village in Semarang City which is located in a strategic area giving rise to slums. This study aims to (1) identify houses including slums and non-slums in Tanjung Mas, (2) find out the slum level of settlements in Tanjung Mas, (3) find out the causes of slums in Tanjung Mas. Object of this study is that there are slums in Tanjung Mas village, while the subject of this study is the patriarchswho reside in slums. This study uses image interpretation analysis techniques and descriptive analysis. Determination of samples using proportional random sampling technique. The results of this study are maps of settlement slums in Tanjung Mas, Semarang City. The slum level of settlements is divided into 4 categories, which are not slums, light slums, medium slums, and heavy slums. The total slum area in Tanjung Mas is 37,34 Ha which is caused by several factors : (1) densification, (2) ageing, and (3)inundation.